The Effect Of Emotional Intelligence And Job Training On Employee Performance Mediated By Organizational Citizenship Behavior At The Bank Indonesia Representative Office In North Sumatra Province - Zulkhaidir Irfan Siregar; Mesra B (International Journal of Management, Economic and Accounting, 2024)
In fact, HR sets the standard in managing a business. Various factors contribute to the prosperity of institutions, organizations, and businesses. However, the human element holds the key to success in achieving this goal. Even if other resources are available, businesses will struggle to function properly without qualified human resources. Human resources are one of the most important factors in a company. The results of this study are as follows: Emotional Intelligence has a positive and significant effect on Employee Performance with a value of 0.332 and a p value of 0.009. Emotional Intelligence had a positive and insignificant effect on Organizational Citizenship Behavior with a value of 0.200 and p values of 0.023. Organizational Citizenship Behavior had a positive and significant effect on Employee Performance with a value of 0.168 and p values of 0.162. Training has a positive and significant effect on Employee Performance with a value of 0.356 and p values of 0.016. The training had a positive and significant effect on Organizational Citizenship Behavior with a value of 0.710 and p values of 0.000. Emotional Intelligence had a positive and insignificant effect on Employee Performance through Organizational Citizenship Behavior with a value of 0.034 and p values of 0.204 Training had a positive and insignificant effect on Employee Performance through Organizational Citizenship Behavior with a value of 0.119 and p values of 0.169.